Design 64 Element Microstrip Antenna Array for Capturing Data from Himawari-8 Satellite - DARMAWAN, MUHAMMAD RIZA; FADHIL, MARTIANA KHOLILA; APRIONO, CATUR (Institut Teknologi Nasional, Bandung, 2025)
This research develops a 64-element microstrip antenna array design using the Dolph-Chebyshev method for capturing Himawari-8 satellite data. Proximitycoupled feed is employed to enhance efficiency and minimize unwanted radiation. Dolph-Chebyshev amplitude distribution is implemented through Wilkinson unequal power dividers and λ/4 transformers for optimizing beamwidth and sidelobe levels. Simulation results show the antenna operates in the frequency range of 4.1036-4.459 GHz with a gain of 23.46 dB at 4.148 GHz. The directional radiation pattern has a 3 dB beamwidth of 6.5° in the E-Plane and 4.9° in the HPlane, with main lobe directions of 0° and 1° respectively. The total antenna dimensions of 752 mm × 627.94 mm × 3.255 mm without requiring a parabolic reflector make it more compact compared to previous designs.